The RING-Type E3 Ligase BOI Interacts with EXO70E2 and Mediates Its Ubiquitination in Arabidopsis - Zhaowu Li; Jianzhong Huang; Yue Hu; Xiaojie Zhou; Xiao Tan; Zhangying Wang; Zhiyong Gao; Xiaoqiu Wu (Life)
The exocyst is a hetero-octameric complex that exhibits significant functional diversity in regulating biological processes and defense responses. In plants, the EXO70 proteins are important components of the exocyst complex and are involved in membrane trafficking, biotic and abiotic interactions, as well as cell wall formation. A previous study has indicated that a member of the EXO subfamily, EXO70E2, interacts with RIN4 to mediate plant immunity. In this study, we found that EXO70E2 interacts with the RING-type E3 ligase Botrytis susceptible1 interactor (BOI), and the C-terminal domain of BOI is necessary for its interaction with EXO70E2. Moreover, the protein level of EXO70E2 was degraded and ubiquitinated by BOI in vitro. Collectively, our study reveals a mechanism for regulating the stability of EXO70E2 by a RING-type E3 ligase BOI-mediated ubiquitination.